Publish Penelitian PENGARUH MEDIA POSTER DAN LEAFLET TERHADAP PENINGKATAN PERILAKU PEGAWAI HOME INDUSTRI DALAM PENGGUNAAN MINYAK GORENG - Nur Afni Maftukhah (Masker Medika, 2023)
Introduction : Community behavior in using cooking oil is generally done many times using the Deep Frying method, namely by immersing all food ingredients in hot oil, the process of heating the oil at a certain temperature, When it is used for frying it will break some of the double bonds (Unsaturated) to become single bonds (Unsaturated). ). Cooking oil used more than three times will experience oxidation which tends to trigger degenerative diseases. Objective : To see the effect of posters and leaflets on the behavior of home industry employees in using cooking oil. Method : This research is quasi-experimental with a pretest-posttest design. This study used a sample of Home Industry Employees consisting of three groups, namely the Media Leaflet Intervention group, the Media Poster Intervention group and the control group, each of which consisted of 18 people. Data collection used a questionnaire and observation and data analysis used the Wilcoxon test. Results : The results of the study proved that the intervention using poster media and leaflet media was effective in increasing the behavior of housewives in the subsequent use of cooking oil with a mean difference value of knowledge leaflet of 6.06, an attitude of 5.95, an action of 6.67 and a mean difference value of knowledge poster of 4.56, attitude of 7.39 and action of 4.39. Discussion : Media influence Posters and Leaflet media are very effective in increasing the behavior of Home Industry employees in using cooking oil.